Project evaluation: collected papers - Harberger, Arnold C. (London: Macmillan, 1972)
This book is about important practical issues that face development planners in the field of project appraisal.
Includes bibliographical references.
oo 06/08/2018
Loans
Keywords: Expenditures, Public; Evaluation research (Social action programs)